Poverty alleviation through cross-sectoral approaches: solutions to accelerate coastal community economy - Almasdi Syahza; Dahlan Tampubolon; Brilliant Asmit; Mitri Irianti (Cogent Social Sciences, 2025)
Coastal communities, particularly in the peatlands, feel neglected by unfair policies. This study seeks to identify poverty alleviation challenges for these communities through a cross-sectoral approach. The sample size is chosen based on local community members and their duration in the village. Village officials and policy implementers provide information on policy forms and impediments. Participatory rural appraisal (PRA) methods are used to gather accurate data, limited to research objectives. Data was analyzed using mixed methods to devise policy solutions for poverty alleviation. Findings indicate that coastal communities face economic challenges due to limited infrastructure, low soil fertility, and rural development disparities. A cross-sectoral approach is advocated, encompassing rural economic development, social progress, cultural development, education, community empowerment, and essential service enhancement. These program implications serve as guidance for policymakers aiming to accelerate coastal economic development, particularly in developing countries.